Evaluación de las estrategias de digitalización para la participación ciudadana en el Gobierno Autónomo descentralizado de El Empalme en el - Macías Zambrano, Cristhian Kleinner (2025)
This research work, entitled "Evaluation of digitalization strategies for Citizen Participation in the Decentralized Autonomous Government of El Empalme in 2024", analyzes the limitations and opportunities in the implementation of technological tools in local public management. The problem focuses on the lack of inclusive and effective digitalization strategies that allow broad and democratic citizen participation, affecting decision-making and governance in El Empalme. The general objective is to evaluate the digital strategies of the GAD of El Empalme to promote citizen participation. Three key aspects are analyzed: the impact of access to technological devices, the factors that influence the use of digital platforms and the budgetary limitations that affect these strategies. The methodology applied is a mixed approach, using surveys and interviews to identify barriers such as the digital divide, lack of training, connectivity problems and budgetary restrictions. The results indicate that, although there are digitalization efforts,